2014
DOI: 10.1590/s0036-46652014000400014
|View full text |Cite
|
Sign up to set email alerts
|

BEHAVIORAL AND MEMORY CHANGES IN Mus musculus COINFECTED BY Toxocara canis AND Toxoplasma gondii

Abstract: Several researchers have stated that parasites can alter the behavior of their hosts, in order to increase the transmission rate, principally when prey-predator relationships are a reliable way of infection transmission. The aim of this study was to verify the occurrence of changes in anxiety and short-term memory patterns in experimentally infected Mus musculus by Toxocara canis and/or Toxoplasma gondii. Forty male Mus musculus (Balb/c) eight-week-old were divided into four groups of 10 mice each. One group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…Doubly infected rats slightly resemble T. canis rats in their behaviour [58]. However, singly infected animals behave similarly to each other [57,58], not illustrating any clear conflict between the parasites. These studies indicate that two parasites with conflicting interests could both have an effect on host behaviour leading to host behaviour that unites traits of hosts that are singly infected by either parasite.…”
Section: Conflict Over Different Specific Interests Can Results In a Cmentioning
confidence: 85%
See 1 more Smart Citation
“…Doubly infected rats slightly resemble T. canis rats in their behaviour [58]. However, singly infected animals behave similarly to each other [57,58], not illustrating any clear conflict between the parasites. These studies indicate that two parasites with conflicting interests could both have an effect on host behaviour leading to host behaviour that unites traits of hosts that are singly infected by either parasite.…”
Section: Conflict Over Different Specific Interests Can Results In a Cmentioning
confidence: 85%
“…In such a case, some functional experiments would be necessary to test whether transmission to each host is maximised by an optimal level of host manipulation or whether one parasite is simply unable to induce the maximal level of host manipulation [25]. Debilitation [103] No clear differences between singly infected hosts [57] Conflict between different transmission strategies (i.e. trophic transmission vs. growth and reproduction on/ in the current host)…”
Section: Conflict Over Host Manipulation Can Occur If Parasites With mentioning
confidence: 99%
“…Similarly, Correa et al (2014) performed a parallel study in mice and found that although mice infected with T. gondii had worse learning and memory compared to controls, mice with both T. gondii and Toxocara performed normally as did mice only infected with Toxocara. It is unclear if a similar effect would be seen in humans.…”
Section: Referencesmentioning
confidence: 95%
“…mansoni [ 188 ] Sarcocystis sp. [ 180 ] Babesia microti [ 98 ] T. spiralis, Entamoeba coli, Dientamoeba fragilis [ 189 ] Mus musculus House mouse Enterocytozoon bieneusi [ 190 ] C. hepaticum [ 191 ] C. parvum [ 183 ] H. nana [ 192 ] H. diminuta, S. muris, T. taeniaeformis [ 193 ] Leishmania major [ 194 ] A.s cantonensis [ 195 ] H. taichui [ 196 ] T. gondii [ 197 ] T. canis [ 198 ] E. multilocularis [ 199 ] Rattus tanezumi Temminck Asian house rats A. cantonensis, Hymenolepis spp., T. taeniaeformis [ 200 ] Syphacia muris, H. diminuta [ 201 ] T. gondii [ 202 ] C. hepaticum [ 203 ] B. microti [ 98 ] Artyfechinostomum malayanum, Echinostoma ilocanum, E. lindoense, H. nana, M. moniliform...…”
Section: Biomphalaria Stramineamentioning
confidence: 99%